Pengaruh Aplikasi Beauveria Bassiana Terhadap Intensitas Serangan dan Mortalitas Larva Spodoptera frugiperda Pada Tanaman Jagung (Zea mays L.). - Alfi Nurwahidah; Trisnan Alif (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
S. frugiperda is a pest that attacks corn plants by eating young shoots/leaves. Leaves that are attacked by S. frugiperda will have many hoisting holes from the edges to the inside. If the attack of S. frugiperda is not immediately controlled, the losses will be crop failure. This study aims to determine the effectiveness of the use of several concentrations of B. bassiana on the intensity of pest attack and mortality of S. frugiperda larvae on maize. This research was conducted in the green house laboratory of Billfath University using a Completely Randomized Design (CRD) consisting of five treatments and four replications. The concentrations of B. bassiana used included K1= negative control (without application), K2= B. bassiana 5 ml/L, K3= B. bassiana 15 ml/L, K4= B. bassiana 25 ml/L and K5= positive control (Chemical insecticide Tiamethoxam 25%) 0.01 g/L. The results showed that the application of the fungus B. bassiana with a concentration of 25 ml/L was effective in controlling S. frugiperda pests on maize (Zea mays L.) which resulted in an attack intensity of 12.50% and larval mortality of 95%.. Keywords: entomopathogenic fungi, B. bassiana, S. frugiperda, corn